Continuous Variable Quantum Teleportation Network. Issue 2 (2nd November 2022) - Shi, Shaoping; Wang, Yajun; Tian, Long; Li, Wei; Wu, Yimiao; Wang, Qingwei; Zheng, Yaohui; Peng, Kunchi
Abstract: Quantum network scales the advantages of quantum communication protocols to more than two detached users, which offers great potential to realize the quantum internet. Here, a fully connected continuous‐variable (CV) quantum teleportation network architecture is presented, in which a squeezed state of light distributes each pair of entangled sideband modes to each communication link that bridges any pair of users. The quantum teleportation scheme is similar to standard two‐party ones for each communication link, without sacrificing communication capability and reliability. The demonstration based on CV‐entangled sideband modes opens an innovative possibility to implement many tasks of deterministic quantum information processing. Abstract : A new scheme of fully interconnected quantum network for continuous variable optical system is developed and demonstrated. The quantum teleportation protocol between any pair of users is realized with ultra‐low losses. Exploiting the distribution scheme of entangled sideband modes from a squeezed state opens an innovative possibility to implement many deterministic quantum information processing tasks.